THE ROLE OF GLYCODELIN IN THE REGULATION OF THE IMMUNE SYSTEM IN THE CONTEXT OF DEVELOPING PREGNANCY - M. S. Bochkova; S. A. Zamorina; V. P. Timganova; P. V. Khramtsov; M. B. Rayev (Медицинская иммунология, 2019)
The review presents data on the role of glycodelin A (GdA, PP14, α2-PEG, EP15, PEP, AUP, PAEP) in regulating the functions of the immune system in the context of the formation of feto-maternal immune tolerance during pregnancy.Glycodelin was first isolated and identified in 1976 by D.D. Petrunin. and Tatarinov Yu.S. with colleagues as a new placenta antigen, which was named chorionic α2-microglobulin. Since then, a huge amount of scientific data has been obtained on the structure, properties, and biological effects of this glycoprotein. This protein has four differentially glycosylated isoforms, namely GdA, GdF, GdC, and GdS, which are secreted in different parts of the reproductive system.The most studied isoform, glycodelin A (GdA), is secreted by the decidual glandular epithelium and accumulates in the amniotic fluid and maternal serum during pregnancy. GdA level is a sign of endometrial fertile function. GdA has diverse biological effects, in particular, it modulates endocrine function and differentiation of trophoblast cells.The role of GdA in the regulation of the immune system is to inhibit the proliferation of T and B lymphocytes, suppress the cytotoxicity of NK cells, induce apoptosis of activated CD4+ cells, monocytes and NK cells, inhibit the activity of cytotoxic T lymphocytes and suppress the functional activity of macrophages and dendritic cells. In addition, GdA increases the level of regulatory T cells, regulates the Th1/Th2 balance towards Th2, and induces a tolerant phenotype of dendritic cells.The immunomodulating activity of GdA depends on the degree of its glycosylation, which, in turn, is associated with the preparation obtaining method. Therefore, the review analyzed the features of the immunomodulating effects of the native and recombinant types of glycodelin on the immune system cells.However, the cumulative effects of GdA on the cells of the immune system make it possible to consider it as one of the main factors shaping the feto-maternal immune tolerance during pregnancy. It is also important to note that clinical studies have revealed a correlation between low levels of circulating GdA and repetitive spontaneous abortions that confirms the importance of this protein in fetoprotection.In general, it is obvious that GdA has the potential as a medicinal preparation for autoimmune deseases treatment, post-transplant complications and in vitro “reprogramming” of autoreactive T-cell clones for further cellular immunotherapy.